Wnt signalling in kidney diseases: dual roles in renal injury and repair. (12th December 2012) - Kawakami, Takahisa; Ren, Shuyu; Duffield, Jeremy S
Abstract Wnt signalling is a complex, highly conserved, cell‐to‐cell communication pathway in multicellular organisms, regulating cell fate, function and phenotype in development, and diseases, including neoplasia. Although the critical role of the Wnt pathway in nephrogenesis is well established, recent investigations have shown its involvement in many adult kidney diseases, including ischaemic kidney injury, glomerular diseases, diabetic nephropathy, interstitial fibrosis and cystic kidney diseases. Overall, activation of the Wnt pathway is deleterious to many chronic diseases of the kidney, contributing to the maintenance of cells in an activated state. In addition, the Wnt pathway is activated during repair and regeneration in animal models of acute ischaemic injury, a scenario that is frequently encountered in human acute kidney injury. This activation recapitulates features of nephrogenesis and appears to play an indispensable role in repair and regeneration in this acute setting. As tools are being developed to regulate the Wnt pathway intracellularly and at the cell surface, the Wnt pathway has become a potential avenue for urgently required novel therapeutics for treating human kidney diseases. In this review, we describe consensus models for major Wnt signalling cascades and then discuss their roles in kidney diseases.